Els verbs semblar(-se), ressemblar i assemblar(-se) en els diccionaris normatius. - RAMOS, JOAN-RAFAEL (Scripta, 2018)
This paper analyses the verbs semblar(-se) ('look like, look, seem'), ressemblar ('look like') and assembler(-se) ('look like') in the academic dictionaries. This information shows that there are differences between meanings of the DLC of the IEC and the DNV of the AVL. Each dictionary approaches its solutions at its nearest speakers and sometimes one of them excludes historical meanings. In the order to know these verbs better, our research analyses these verbs in Old Catalan and describes their meanings and syntactic structures. The study is based on a data corpus (CICA) from the 13th to the 16th century. It provides a systematic and comprehensive demonstration of the semantic and syntactic tendencies of this period and it advises the need to modify some dictionary entries.